Factors associated with non-utilization of freely acquired insecticide-treated nets (ITNs) in a rural agrarian community of North-Western Nigeria - Abdulrazaq Abdullahi Gobir,; Mohammad Nasir Sambo,; Suleman Idris Hadejia, (penerbit ukm, 2013)
Malaria Programme of scaling up ITN use, the Nigerian Government distributed free ITNs to many households in the country. However, several factors were associated with non-utilisation of the ITNs. This cross-sectional descriptive study was conducted to assess such factors in Gimba village, a rural community of Kaduna State, Nigeria. It was conducted during Community Diagnosis practical fi eld posting of trained fi nal year medical students of Ahmadu Bello University, Nigeria, in July 2012. An interviewer-administered questionnaire was used to collect data from all households in the community. Multivariate logistic regression analysis was done using STATA (Version 11. Stata Corporation, 2009). Most of the households own at least, one freely acquired ITN (82%). However, in 40.8% of such households, no member slept under an ITN the night before the survey. Farmers were more unlikely to use an ITN compared to non-farmers (RR = 1.89; 95% C.I = 0.78 –2.91). Instead of ITN, some farmers use “otapiapia” a cheap, unpatented, locally made pesticide for controlling mosquitoes. Also, respondents with low scores on malaria risk perception were more unlikely to use an ITN compared to those with high scores (RR = 1.08; 95% C.I = 0.94 – 1.23).The result indicated that several factors were associated with non-utilization of freely acquired ITNs. It is recommended that ITN distribution should be accompanied by Health Education on Malaria.